2020
DOI: 10.1186/s12889-020-09016-6
|View full text |Cite
|
Sign up to set email alerts
|

Milk-borne bacterial health hazards in milk produced for commercial purpose in Tigray, northern Ethiopia

Abstract: Background: Milk being a suitable medium for bacterial growth, it can serve as a source of bacterial contamination. Pathogenic bacteria in milk pose a serious health threat to humans and constitute about 90% of all dairy-related diseases. However, there are few studies that examined the health hazards of raw milk consumption in Ethiopia. Therefore, the objective of this study was to assess the prevalence of bacterial contamination and associated factors in milk produced for commercial purpose in Tigray region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 12 publications
7
34
1
Order By: Relevance
“…MBD is quite a common public health problem, because it not only has an impact on human health, also has an impact on the health of dairy cows, especially in the milk production and quality sector. 22 Several previous studies have reported that the incidence of contaminated milk by S. aureus resistant to antibiotics is found in both developed and developing countries. 23 Improper and unhygienic handling of milk, especially during the milking process, plays an important role in the occurrence of milk contamination.…”
Section: Discussionmentioning
confidence: 99%
“…MBD is quite a common public health problem, because it not only has an impact on human health, also has an impact on the health of dairy cows, especially in the milk production and quality sector. 22 Several previous studies have reported that the incidence of contaminated milk by S. aureus resistant to antibiotics is found in both developed and developing countries. 23 Improper and unhygienic handling of milk, especially during the milking process, plays an important role in the occurrence of milk contamination.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to air, packaging, drains, and employees' contamination [17]. One study found that hygiene practices are insufficient in the entire milk production system in developing countries [28].…”
Section: Bacterial Diversity Of Hygiene Indicatorsmentioning
confidence: 99%
“…Several studies find that a wider diversity of market channels is helpful to support access and affordability of food, as well as food safety goals (Phiri et al, 2021;Reddy et al, 2020). In addition, Berhe et al (2020) and Khadka et al (2017) point to the importance of joint investments to support supply chain coordination between multiple stakeholders in order to better guarantee compliance.…”
Section: Private Sector As Lead Innovation Agentmentioning
confidence: 99%